Evaluasi Kinerja Petugas Distribusi Berkas Rekam Medis Rawat Jalan di RSUD dr. Saiful Anwar Malang - Najla Kamil; Novita Nuraini; Maya Weka Santi (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Provision of outpatient medical record documents is the time required to provide medical recorddocuments from the patient registering to the examination. According to Minister of Health Decree No. 129of 2008 which states that the provision of outpatient medical record files is less than 10 minutes. Based onthe observation time of providing medical record documents at Dr. Hospital. Saiful Anwar Malang for morethan 10 minutes. The longest time for providing medical record documents is in the process of distributingmedical record documents from the distribution rack to the clinic for 14.84 minutes. To find the factors thatcause delays in the distribution of food, an evaluation of the performance of the distribution officers iscarried out with the performance theory of Motivation, Opportunity, and Ability. The aim is to determine thedelay factor in the distribution of medical record documents which causes the quality of hospital services todecrease. Based on observations, interviews and documentation, it is known that the factors causingdelays in distribution are lack of motivation and sanctions, lack of discipline among officers and no clearSOP regarding the distribution of medical records. Then there is a need for clear performance monitoringand preparation of SOPs related to the distribution of medical record documents.